2021
DOI: 10.3390/ijms222111969
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Molecular Structure of Carbohydrates and Their Dynamic Hydration Shells Revealed by Terahertz Time-Domain Spectroscopy

Abstract: Despite more than a century of research on the hydration of biomolecules, the hydration of carbohydrates is insufficiently studied. An approach to studying dynamic hydration shells of carbohydrates in aqueous solutions based on terahertz time-domain spectroscopy assay is developed in the current work. Monosaccharides (glucose, galactose, galacturonic acid) and polysaccharides (dextran, amylopectin, polygalacturonic acid) solutions were studied. The contribution of the dissolved carbohydrates was subtracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 106 publications
(161 reference statements)
1
9
0
Order By: Relevance
“…It is sensitive not only to the primary strongly bound hydrate shell but also to more distant areas of hydration with altered dynamics of water molecules [33][34][35]. In our previous work, we analyzed solutions of proteins [36], phospholipids [35], nucleic acids [37,38], and sugars [39] using the THz time-domain spectroscopy (THz-TDS) method, which confirms the great possibilities of this method in the study of hydration. Also, in a recent work [40] on the study of aqueous solutions of alcohols by THz spectroscopy, it was shown that this method is very informative in the analysis of intermolecular hydrogen bonds and molecular micro-inhomogeneities.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is sensitive not only to the primary strongly bound hydrate shell but also to more distant areas of hydration with altered dynamics of water molecules [33][34][35]. In our previous work, we analyzed solutions of proteins [36], phospholipids [35], nucleic acids [37,38], and sugars [39] using the THz time-domain spectroscopy (THz-TDS) method, which confirms the great possibilities of this method in the study of hydration. Also, in a recent work [40] on the study of aqueous solutions of alcohols by THz spectroscopy, it was shown that this method is very informative in the analysis of intermolecular hydrogen bonds and molecular micro-inhomogeneities.…”
Section: Introductionsupporting
confidence: 56%
“…In this case, all three permittivities are complex functions of frequency, i.e., DS. We used a similar approach to separating the dielectric contributions of phases for sugar solutions earlier [39].…”
Section: Subtracting the Contribution Of Sugars From Ds Of Their Solu...mentioning
confidence: 99%
“…These results could be explained by looking into the chemical structures: 17 and SER compounds are epimers in the C‐4 position, being the orientation of the OH(4) group the only difference. According to the literature, [50] this behavior is strictly connected to a different ability of matching the tetrahedral hydrogen bond network of water. Sugars with an axial OH(4) group, such as galactose, match the three‐dimensional water structure much worse than sugars with an equatorially‐oriented OH(4), as in the case of glucose.…”
Section: Resultsmentioning
confidence: 98%
“…This may arise from the intrinsic geometry of the hydroxy groups of GalNAc and GlcNAc. The water molecules directly bound on sugars potentially restructure surrounding water molecules mediating between the first hydration shell and bulk water [14] . The water molecules in this interfacial water phase between sugar and bulk water phase are orientationally disordered compared with the bulk water (Figure 7).…”
Section: Resultsmentioning
confidence: 99%